On-demand platforms and pricing: how platforms can impact the informal urban economy, evidence from Bengaluru, India. (1st January 2020) - Surie, Aditi
Abstract : Pricing is one of the most powerful mechanisms platform firms use to internally regulate demand and supply, withstand competitors and achieve profitability (Rochet & Triole, 2003). This article uncovers the effects that platform pricing logics have on existing labour markets within the city of Bengaluru. For this article the platform serves as the object of study, i.e. in determining earnings for service providers for various purposes (like subsidising products by (mis)matching service price and earnings) and it serves as a means to enter the service labour market as it exists in the city. This article looks at how platform service fees, with the particular set of logics of the two-sided markets and intra-capitalist competition, impact adjacent enterprises (informal, own account enterprises) providing the same services. Carpentry, electrical work and plumbing are services with a long history in the city and their breadth of service was not created as a result of the platform (compared to food delivery, for example). Rarely do minimum wage floors factor into the service fee negotiation between providers and clients. The platforms' market does have that impact, creating a standard around their base fee, undercutting the more tacit ways in which workers negotiate their service fees. This article uses ethnographic data from interviews with people working on Urban Company and Housejoy platforms in carpentry, electrical work and plumbing, collected in Bengaluru in 2017-18.